2020
DOI: 10.1093/jpe/rtaa075
|View full text |Cite
|
Sign up to set email alerts
|

Similarity in fine-to-total root mass ratio leads to comparative plant–soil feedbacks between co-occurring native and invasive plants

Abstract: Aims Soil biota can affect plant-plant interactions and non-native plant invasions via plant-soil feedback (PSF). Understanding the drivers underlying interspecific variations in PSF is important for predicting the role of soil biota in non-native plant invasions. Recent studies found that PSF could be predicted by plant traits. The success of plant invasions is also linked with plant traits, suggesting a potential linkage between PSF and plant invasion via plant traits, but has not yet been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…This yielded 18 studies, which along with the studies from Crawford et al. ( 8 ) generated a total of 50 papers from which we extracted information ( 24 , 26 , 28 , 38 , 43 , 46 90 ). If a study had multiple experiments across different soil sources, resource gradients, or competition intensities, we compiled data separately for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…This yielded 18 studies, which along with the studies from Crawford et al. ( 8 ) generated a total of 50 papers from which we extracted information ( 24 , 26 , 28 , 38 , 43 , 46 90 ). If a study had multiple experiments across different soil sources, resource gradients, or competition intensities, we compiled data separately for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we did not find support for our third hypothesis. Other studies also showed that species origin is often not the most important factor shaping plant–soil interactions (Tang et al, 2020; Wilschut et al, 2019). For instance, in a study integrating a large‐scale field survey and manipulated experiments with 66 species from 18 families, we found that plant evolution overwhelmed species origin in shaping rhizosphere fungal communities (Wei et al, 2021).…”
Section: Discussionmentioning
confidence: 96%